The Effect of Sweet Potato Leaf Decoction and Iron Tablet against Increased Hemoglobin Levels in Pregnant Women - Naomi Christina Hutabarat; Melyana Nurul Widyawati (Universitas Triatma Mulya, 2018)
Background. Anemia in pregnant women is currently a national problem of maternal and child health in Indonesia. Based on Riskesdas data in 2013, the prevalence of pregnant women with anemia in Indonesia was 37.1%, namely pregnant women with Hb levels of less than 11.0 grams/dl, with almost the same proportion in urban areas (36.4%) and rural (37.8%). The program of giving at least 90 iron tablets during pregnancy is an important component in efforts to prevent iron deficiency anemia. However, the absorption of non-heme iron can be increased by consuming vitamin C from fruits, vegetables, or other food factors that facilitate absorption. One of them is the local wisdom of Pekalongan Regency, namely sweet potato leaf which is used as a vegetable. The purpose of this study was to determine maternal hemoglobin levels before and after being given the treatment of boiling sweet potato leaves and iron tablets. Methods. This research is a pre-post experiment research (mini-research) with a sample of 4 people who will be assessed and assessed for hemoglobin levels before and after treatment. Results. The result shows that the treatment of 100 grams of sweet potato leaves decoction for 10 days can increase hemoglobin levels in each respondent at R1 1.7 gr%, R2 2.1, R3 2.2, and R4 2.7 gr%. Conclusion. Further research is needed to prove the stronger benefits of sweet potato leaf decoction in helping to increase Hb levels of pregnant women by increasing the number of samples and testing hematocrit levels in the blood.